2020
DOI: 10.5653/cerm.2019.03216
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of the outgrowth model for evaluating the implantation competence of blastocysts

Abstract: The implantation process is highly complex and difficult to mimic <i>in vitro</i>, and a reliable experimental model of implantation has yet to be established. Many researchers have used embryo transfer (ET) to assess implantation potential; however, ET with pseudopregnant mice requires expert surgical skills and numerous sacrificial animals. To overcome those economic and ethical problems, several researchers have tried to use outgrowth models to evaluate the implantation potential of embryos. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“… 39 , 40 , 41 , 42 In addition, the blastocyst outgrowth assay has been used as an in vitro implantation model. 43 We then cultured E3.5 blastocysts in KSOM with or without 10% FBS for 24, 48, or 72 h after removing ZP, and compared the morphology and CDX2 expression in the mural TE. This revealed that, whereas blastocysts cultured in KSOM maintained an expanded state and never showed outgrowths, blastocysts cultured in KSOM with 10% FBS (KSOM + FBS) developed outgrowths.…”
Section: Resultsmentioning
confidence: 99%
“… 39 , 40 , 41 , 42 In addition, the blastocyst outgrowth assay has been used as an in vitro implantation model. 43 We then cultured E3.5 blastocysts in KSOM with or without 10% FBS for 24, 48, or 72 h after removing ZP, and compared the morphology and CDX2 expression in the mural TE. This revealed that, whereas blastocysts cultured in KSOM maintained an expanded state and never showed outgrowths, blastocysts cultured in KSOM with 10% FBS (KSOM + FBS) developed outgrowths.…”
Section: Resultsmentioning
confidence: 99%
“…Under optimal loading conditions, microfluidic device culture had no impact on blastocyst cell number and blastomere partitioning between the ICM and TE. Furthermore the blastocysts grown in microfluidic devices demonstrated equivalent capacity for hatching and out growth in vitro, factors which are indicative of implantation potential in vivo [77]. Taken together, these data indicate that the novel microfluidic device presented here is embryocompatible and can successfully be used to support healthy embryo development to the blastocyst stage without the need for media changes or oil overlay.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the blastocysts grown in microfluidic devices demonstrated equivalent capacity for hatching and out growth in vitro, factors which are indicative of implantation potential in vivo. 78 Taken together, these data indicate that the novel microfluidic device presented here is embryo-compatible and can successfully be used to However, in this work gene expression levels were measured using relative quantification method, which did not allow to obtain information on the absolute expression value for each gene. Further analyses might use absolute quantification methods to measure expression levels of selected genes, to directly compare our findings with available gene expression datasets and elucidate specific impact of the gene alteration on embryo culture.…”
Section: Discussionmentioning
confidence: 94%